A learning approach for improving sanitation and hygiene services: experiences from PILS in Northern Uganda - Valerie Bey (2013)
Performance Improvement through Learning on Sanitation (PILS) was a district- and sub-county-based learning initiative aiming for increased performance, innovation and change in rural sanitation and hygiene in Northern Uganda. PILS was implemented in 2009-2012, shortly after the end of a more than two decades long civil war. In the midst of this transition phase from conflict to peace, local populations, as well as agencies and organisations involved in the provision of sanitation and hygiene services, were facing drastic changes in context, roles and responsibilities, relationships, resources, etc. PILS’ approach included the facilitation of multi-stakeholder learning sessions, action research, capacity building and documentation. These led to improved stakeholders coordination, the prioritisation of sanitation and hygiene, and an increase in latrines coverage. The learning approach adopted for PILS undeniably supported stakeholders in the changed context for improving rural sanitation and hygiene.